Prosecutorial Use of Victim Video Statements in Domestic Violence Cases - Backes, Bethany (Crime & delinquency, 2022)
Prosecuting agencies frequently dismiss domestic violence cases due to lack of adequate evidence and limited victim participation in the case. Evidence-based prosecution asserts high quality evidence can enhance prosecutorial decision-making and reduce the reliance on victims. Video-recorded victim statements offer a potential improvement to evidence quality by capturing additional visual and factual information for prosecutors to determine applicable charges. This qualitative study examines data from six prosecution agencies in a southwestern state to understand how they use video-recorded victim statements to inform their decision-making. Findings provide preliminary evidence on the strength of video-recorded statements in offering more information on the victim, crime, and scene; strengthening negotiations with defense counsel; enhancing case strategies; and improving victim engagement. Implications for continued research and practice are discussed.